Secularization and Educational Projects during the Rule of Hetman Kyrylo Rozumovsky in 1750–1764 - Маслійчук, Володимир (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2016)
Secularization appears to be crucial in cultural and educational activities of Hetman Kyrylo Rozumovsky. Restriction of rights of the Church, lack of concideration of the established practices and an attempt to create a secular University in Baturyn confirm the substantial plans of Hetman. Here we can observe how his mentor Hryhoriy Teplov influenced theHetman's policy. But in the early 1760 this policy changed: cossacs’ elite pressed for the reform of the Kiyiv Academyinto secular educational establishment with the theological faculty, teaching the cossacks’ children corresponded withthe traditional educational practices. The Rozumovsky’s time caused significant contradictions in secular processes in the left-bank Ukraine.